REVIEW AND NEW DATA ON UPLIFT RATES AT THE W TERMINATION OF THE CORINTH RIFT AND THE NE RION GRABEN AREA (ACHAIA, NW PELOPONNESOS) - Palyvos, N.; Sorel, D.; Lemeille, F.; Mancini, M.; Pantosti, D.; Julia, R.; Triantaphyllou, M.; De Martini, P. M. (Bulletin of the Geological Society of Greece, 2007)
We review and present new geochronological data on the uplifted Middle-Late Pleistocene marine deposits at the western termination of the Corinth Rift and the Rion area. Geomorphological and geological observations define the general morphotectonic context of these deposits, which predicts a pattern of differential uplift. Uplift rate estimates based on previous geochronological data (ranging from 0.4 to 6 mm/yr) are discussed in the proposed morphotectonic context of differential uplift, together with estimates from new geochronological data. Based on the data available for post-MISl 1 marine deposits, we conclude that time-averaged uplift rates in the last 300-200 lea have been higher than ca. 1.8 mm/yr at the areas of faster uplift (e.g. Profus Elias, Ano Kastritsi). To define just how higher than 1.8 mm/yr they have been, and to cross-check the validity of very high uplift rate estimates (> 4 mm/yr) existing in the bibliography, more datings than those available are required.